Comparison of the efficacy of rechallenge with anti-PD-1 antibody monotherapy and BRAF/MEK inhibitor in advanced malignant melanoma: A single-center, retrospective cohort study - Ken Horisaki; Shusuke Yoshikawa; Wataru Omata; Arata Tsutsumida; Yoshio Kiyohara (Dermatologica Sinica)
Anti-PD-1 antibody monotherapy (anti-PD-1) and BRAF/MEK inhibitors (BRAF/MEKi) are currently recognized as effective treatments for advanced-stage malignant melanoma (MM) and have become standard systemic treatments. However, many patients with MM still do not benefit from these therapies. In this study, we aimed to examine the efficacy of rechallenge with the same agents in patients with stage IV MM who experienced progressive disease after treatment with anti-PD-1 or BRAF/MEKi. We analyzed 48 patients who experienced tumor progression after receiving either PD-1 or BRAF/MEKi as systemic therapy and were rechallenged with the same type of agents. The BRAF/MEKi rechallenge group had a better overall response rate than the anti-PD-1 rechallenge group (14.3% vs. 0%, P = 0.08). The disease control rate was significantly better in the BRAF/MEKi group than in the anti-PD-1 group (50.0% vs. 8.8%, P = 0.003). The BRAF/MEKi group showed significantly better progression-free survival than the anti-PD-1 group (median time: 3.0 vs. 2.1 months, P = 0.025). The results of this study indicate that the BRAF/MEKi rechallenge may be more beneficial than anti-PD-1 if the patient is BRAF mutation-positive. In BRAF mutation-negative patients, anti-PD-1 rechallenge is rarely effective but may be an option if a response is achieved with the initial systemic therapy with anti-PD-1.